The relationship of physical balance to the utilization of pelleted and non-pelleted rations for lambs. - Menzies, C.S.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Physical balance of lamb-fattening rations has been studied in this project for several years. These tests have been designed to study the effect of pelleting rations of varying proportions of roughages and concentrates upon feed-lot performance and feed efficiency compared with similar non-polleted rations. For the past three years both dehydrated and field-cured alfalfa hay have been used as roughages.
Keywords: Sheep; Pelleted rations; Non-pelleted rations